2022
DOI: 10.1038/s41567-022-01516-z
|View full text |Cite
|
Sign up to set email alerts
|

Water cycles in a Hadean CO2 atmosphere drive the evolution of long DNA

Abstract: Dew is a common form of water that deposits from saturated air on colder surfaces. Although presumably common on primordial Earth, its potential involvement in the origin of life in early replication has not been investigated in detail. Here we report that it can drive the first stages of Darwinian evolution for DNA and RNA, first by periodically denaturing their structures at low temperatures and second by promoting the replication of long strands over short, faster replicating ones. Our experiments mimicked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Moreover, we have shown that efficient strand separation can be achieved by low sodium concentrations, triggered by microscale water cycles within heated rock pores. [35,36] Our very preliminary digestion studies suggest a considerable backbone heterogeneity (2´-5´ and 3´-5´) within the polymers. However, a full quantitative treatment is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Moreover, we have shown that efficient strand separation can be achieved by low sodium concentrations, triggered by microscale water cycles within heated rock pores. [35,36] Our very preliminary digestion studies suggest a considerable backbone heterogeneity (2´-5´ and 3´-5´) within the polymers. However, a full quantitative treatment is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 79%
“…A length-selective enzymatic DNA replication was reported recently within this setting, indicating the possible continuity of prebiotic chemistry in such a setting. [36] We observed all the dimer sequence combinations and most of the trimers (Figure 3c). However, the tetramers and pentamers show sequences rich in G. The length selectivity of the HPLC allowed the detection of longer sequences, but the isotopic fit to the raw mass spectra provided by our LabView-based analysis showed that longer species with concentrations lower than 0.2 µM were lost in the background noise of the mass spectra.…”
Section: Polymerisation Of Cnmp In a Heated Rock Pore Mimicmentioning
confidence: 85%
See 3 more Smart Citations